Characterization of a narrowband Raman MOPA with short master oscillator - Siekiera, Alexander; Engelbrecht, Rainer; Nothofer, Andreas; Schmauß, Bernhard (SPIE 8237 Photonics West, 2012)
Raman fiber lasers (RFL) with a narrow spectral bandwidth are important light sources, e.g. for applications that require second-harmonic generation. Non-linear optical processes within the fiber like four-wave mixing (FWM) lead to spectral broadening, due to the generation of frequency components outside of the initial laser bandwidth. This mainly results from FWM of the longitudinal modes generated in the laser cavity. Consequently a reduced number of modes with increased frequency spacing, which is obtained by using a short laser cavity, is expected to reduce the spectral broadening. We investigate a Raman master oscillator power amplifier (MOPA) configuration, consisting of a RFL with a very short cavity length of 17 cm and a subsequent Raman amplifier of 55 m length. Pumping with 8 W power of an Ytterbium-doped fiber laser at 1100 nm, the Stokes wave at 1151 nm is generated, yielding 0.7 W Stokes power with a narrow full-width at half-maximum bandwidth of 60 pm at the MO output. From the measured frequency spacing of 607 MHz between the longitudinal modes a maximum number of 24 modes can be calculated to oscillate within the bandwidth of the MO output. The residual pump power is used to amplify the Stokes wave in a subsequent Raman amplifier. At the MOPA output the amplified Stokes power is 4.3 W with a strongly broadened bandwidth of 328 pm. Thus our results show that even for a Stokes wave with only few longitudinal modes at the MO output, strong FWM induced spectral broadening occurs within the amplifie
lhft_intern.bib::Siekiera2012